The impact of cognitive map quality and expert testimony on juror decisions and perceived credibility of eyewitnesses - Simmons, Justin Parker (2016)
An eyewitness to a crime is often asked to create a hand drawn psychological map of the crime scene in terms of the placement of buildings, people, and other objects. Psychological maps, also referred to as “sketch maps,” are a physical representation of one’s mental map of a particular location. Sketch maps are often submitted as evidence and presented to jury members during trial. Information from these maps can be used to provide information such as entrance and exit into the crime scene by the perpetrator, relative distance between eyewitness and perpetrator, and other information critical to jurors’ evaluations of eyewitness evidence and testimony. Previous research has shown that the quality of a sketch map can be manipulated with instructions (Simmons, Heddinger, Hurd, & MacLin, 2014). Because sketch maps may influence juror decision making, the current study examined the relationship between the quality of a sketch map and perceived credibility of the eyewitness. Participants received eyewitness testimony including a sketch map, lineup identification, and the confidence level of the eyewitness identification. Additionally, the experimental groups received expert testimony either supporting a positive correlation between map quality and identification accuracy, refuting the correlation, or no expert testimony. After reviewing the materials, participants evaluated the credibility of the eyewitness and arrived at a verdict for the defendant based on the evidence provided. When given high quality sketch maps, participants found eyewitnesses to be more credible and arrived at more guilty verdicts compared to low quality sketch maps. Frequency of guilty verdicts also increased with expert testimony, regardless of the stance of the expert